Cloud-Based Virtual Learning Environment Model: A Delphi Study: A Delphi Study - Rezqallah Malkawi, Aminah; Shahbani Abu Bakar, Muhamad; Md Dahlin, Zulkhairi (Law, State and Telecommunications Review, 2024)
[Purpose] With the recent technological advancement that the educational sector is facing nowadays, exploring, and evaluating the requirements of such technologies is becoming an important phase to ensure its usability, adaptability, and efficiency before official development and adoption. Thus, this study employed the Delphi technique to gather experts’ opinions and reach a consensus on the critical requirements of a virtual learning environment (VLE) based on cloud computing technology. The output of this study proposes a validated cloud-based virtual learning environment (CBVLE) model for use within the teaching and learning environment in Saudi Arabia’s higher education institutions (HEI). [Methodology/Approach/Design] This study employed the Delphi technique to validate a CBVLE model by conducting three different questionnaire rounds for the same panel of 19 experts to reach a consensus of views on the ideal CBVLE model to be used within the targeted environment. [Practical Implications] The paper highlights the main legal, educational, operational, and quality requirements and factors to consider before developing any CBVLE model, such as cultural influence. The results of this study are expected to provide valuable insights for educators and administrators, along with performing a guideline for researchers in designing and implementing effective, usable, and adoptable CBVLE.